Introduction to thermal and fluids engineering - Jensen, Michael K., ....-; Kaminski, Deborah A., ....- (Hoboken : Wiley, 2005)
This innovative book uses unifying themes so that the boundaries between thermodynamics, heat transfer, and fluid mechanics become transparent. It begins with an introduction to the numerous engineering applications that may require the integration of principles and tools from these disciplines. The authors then present an in-depth examination of the three disciplines, providing readers with the necessary background to solve various engineering problems. The remaining chapters delve into the topics in more detail and rigor. Numerous practical engineering applications are mentioned throughout to illustrate where and when certain equations, concepts, and topics are needed. A comprehensive introduction to thermodynamics, fluid mechanics, and heat transfer, this title: Develops governing equations and approaches in sufficient detail, showing how the equations are based on fundamental conservation laws and other basic concepts. Explains the physics of processes and phenomena with language and examples that have been seen and used in everyday life. Integrates the presentation of the three subjects with common notation, examples, and problems. Demonstrates how to solve any problem in a systematic, logical manner. Presents material appropriate for an introductory level course on thermodynamics, heat transfer, and fluid mechanics.